Long-Term Outcomes, Education, and Occupational Level in Cochlear Implant Recipients Who Were Implanted in Childhood. Issue 5 (September 2017) - Illg, Angelika; Haack, Marius; Lesinski-Schiedat, Anke; Büchner, Andreas; Lenarz, Thomas
Abstract : Objectives: To document the long-term outcomes of auditory performance, educational status, vocational training, and occupational situation in users of cochlear implants (CIs) who were implanted in childhood. Design: This retrospective cross-sectional study of 933 recipients of CIs examined auditory performance, education and vocational training, and occupational outcomes. All participants received their first CI during their childhood between 1986 and 2000. Speech comprehension results were categorized using the categories of auditory performance (CAP) arranged in order of increasing difficulty ranging from 0 to 8. 174 of the 933 pediatric recipients of CIs completed a self-assessment questionnaire regarding their education and occupational outcomes. To measure and compare school education, qualifications were converted into International Standard Classification of Education levels (ISCED-97). Occupations were converted into International Standard Classification of Occupation-88 skill levels. Data from the German General Social Survey (Allgemeine Bevölkerungsumfrage der Sozialwissenschaften/ALLBUS) for 2012 were used as a basis for comparing some of the collected data with the general population in Germany. Results: The results showed that 86.8% of the 174 participants who completed the survey used their devices more than 11 hr per day. Only 2% of the surveyed individuals were nonusers. Median CAP was 4.00 (0 to 8). Age at implantation was significantly correlated with CAP level ( r = −0.472; p < 0.001). The mean ISCED level of the 174 surveyed recipients was 2.24 (SD = 0.59; range: 1 to 3). A significant difference ( p = 0.001) between users' ISCED levels and those ofALLBUS 2012 respondents was found. Participants' ISCED levels and maternal educational levels were significantly correlated ( r = 0.271; p = 0.008). The International Standard Classification of Occupation-88 skill levels were as follows: 5% achieved skill level 1; 77% skill level 2; 16% skill level 3; and 5% skill level 4. The average skill level achieved was 2.24 (range 1 to 4; SD = 0.57) which was significantly poorer ( t (127) = 4.886; p = 0.001) than the mean skill level of theALLBUS 2012 respondents (mean = 2.54; SD = 0.85). Conclusions: Data collection up to 17.75 (SD = 3.08; range 13 to 28) years post implant demonstrated that the majority of participants who underwent implantation at an early age achieved discrimination of speech sounds without lipreading (CAP category 4.00). Educational, vocational, and occupational level achieved by this cohort were significantly poorer compared with the German and worldwide population average. Children implanted today who are younger at implantation, and with whom more advanced up-to-date CIs are used, are expected to exhibit better auditory performance and have enhanced educational and occupational opportunities. Compared with the circumstances immediately after World War II in the 20th century, children with hearing impairment who use these implants have improved prospects in this regard. Abstract : Supplemental Digital Content is available in the text.